Multimodal transport as a sustainable transport for the chemical industry: primary qualitative research - Chocholáč, Jan; Hyršlová, Jaroslava (Oeconomica, 2018)
Increasing transport performance, more traffic accidents and efforts to respect sustainable development make companies look for optimal transport solutions. The paper deals with the utilization of multimodal transport in the framework of transport of chemical goods in selected Czech Republic chemical industry companies. The primary objective of the paper is to map the motivation of the selected chemical industry companies for shifting the transport to multimodal transport.
Multimodální doprava jako udržitelná doprava pro chemický průmysl: primární kvalitativní výzkum
Keywords: multimodal transport; chemical industry; sustainable transport; sustainable development; multimodální doprava; chemický průmysl; udržitelná doprava; udržitelný rozvoj